2018
DOI: 10.1111/fare.12336
|View full text |Cite
|
Sign up to set email alerts
|

Coming Out and Getting Back In: Relationship Cycling and Distress in Same‐ and Different‐Sex Relationships

Abstract: Objective To examine the role of on–off relationship cycling in psychological distress for individuals in same‐ and different‐sex relationships. Background Relationship processes have a robust effect on individual well‐being, and dissolution is associated with psychological distress that is normative and typically short‐lived. A prolonged history of terminating a relationship and then reconciling (i.e., on–off cycling), however, may facilitate more pervasive symptomology. Moreover, researchers have indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 80 publications
(131 reference statements)
0
27
0
Order By: Relevance
“…The paucity of data on sexual‐minority adults, particularly longitudinal data, means that few studies explore whether the factors shaping the union formation processes of same‐sex individuals are similar to or different from those influencing different‐sex adults (although see Orth & Rosenfeld, ). Nonetheless, the growing cultural acceptance of same‐sex partnerships, reinforced by the legalization of same‐sex marriages, arguably strengthens commitment and stability in the form of long‐term and monogamous relationships, much like it does for different‐sex relationships (Joyner, Manning, & Bogle, ; Lau, ; Monk, Ogolsky, & Oswald, ). Variation in institutionalization of same‐sex marriage across countries suggests one important mechanism shaping both relationship formation processes and union stability (Joyner et al, ; Potârcă et al, ), given the research that legal formalization is associated with greater relationship stability (Whitton, Kuryluk, & Khaddouma, ).…”
Section: Research Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…The paucity of data on sexual‐minority adults, particularly longitudinal data, means that few studies explore whether the factors shaping the union formation processes of same‐sex individuals are similar to or different from those influencing different‐sex adults (although see Orth & Rosenfeld, ). Nonetheless, the growing cultural acceptance of same‐sex partnerships, reinforced by the legalization of same‐sex marriages, arguably strengthens commitment and stability in the form of long‐term and monogamous relationships, much like it does for different‐sex relationships (Joyner, Manning, & Bogle, ; Lau, ; Monk, Ogolsky, & Oswald, ). Variation in institutionalization of same‐sex marriage across countries suggests one important mechanism shaping both relationship formation processes and union stability (Joyner et al, ; Potârcă et al, ), given the research that legal formalization is associated with greater relationship stability (Whitton, Kuryluk, & Khaddouma, ).…”
Section: Research Themesmentioning
confidence: 99%
“…Current research has only just begun to study various patterns and conditions that apply to union‐formation processes observed among sexual minorities (see Reczek, ). Comparisons of opposite‐sex and same‐sex cohabiting partners are now conventional (Monk et al, ), especially as nationally representative data that includes gay and lesbian couples has become more commonplace. New research has begun to explore mate selection processes (Lamont, ; Potârcă et al, ), but more research is needed on the implications for union quality and stability, health and emotional well‐being, poverty and affluence, and other dimensions of well‐being.…”
Section: Research Themesmentioning
confidence: 99%
“…A paradox of ambivalence in on-again/off-again relationships Relationships that might be particularly prone to relational ambivalence are on-off relationships (Joel et al, 2018). Up to two third of individuals will experience an onoff relationship, and about a third of current daters report their relationship has had a cyclical nature (Dailey et al, 2009;Halpern-Meekin et al, 2013a;Monk et al, 2018). Yet, these relationships entail lower relational quality and an increased chance of aggression and abuse (Dailey et al, 2009;Halpern-Meekin et al, 2013b;Monk, 2017;Vennum & Johnson, 2014).…”
Section: Post-dissolution Ambivalence and Relationship Reconciliationmentioning
confidence: 99%
“…Second, results may differ depending on the number of, and spacing between, waves in different data sets (e.g., Eggleston et al, 2004). Third, future work should examine the implications of making multiple transitions (e.g., divorce and remarriage) as well as transitioning back into a relationship that previously ended (e.g., separation and reconciliation; Monk, Ogolsky, & Oswald, 2018) for group-based modeling analyses. Last, future research should examine how these sampling criteria influence other types of marital functioning (e.g., negative communication), as global indicators of marital functioning might be less variable than behavioral indicators (e.g., Lavner, Karney, & Bradbury, 2016).…”
Section: Implications and Future Directionsmentioning
confidence: 99%